STM investigation of carbon nanotubes connected by functional groups - Koos, A; Horvath, Z; Osvath, Z; Tapaszto, L; Niesz, K; Konya, Z; Kiricsi, I; Grobert, N; Ruhle, M; Biro, L (2003)
Chemical functionalization of carbon nanotubes (CNTs) is essential for many applications. Attachment of functional groups to nanotubes can dramatically increase the solubility of the nanotube material. Sidewall functional groups should react with polymers and improve the mechanical properties of nanocomposites. Tubes interconnected by chemical bonds will have a reduced contact resistance and can be used for interconnection purposes in nanoscale circuits. Carbon nanotubes covered with functional groups attached to their exterior wall were analyzed using scanning tunneling microscopy (STM) and TEM. The functionalization was carried out in three steps: acid treatment in H2SO4/HNO3 (3:1) mixture, reaction with SOCl2 and reaction with diaminopropanol (DAP). The binding force between the nanotubes connected by functional groups and the mechanical stability of the connection was investigated. (C) 2003 Elsevier B.V. All rights reserved.